Catalytic Hydrogenation of Acetone to Isopropanol: An Environmentally Benign Approach - Ateeq Rahman (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2010)
The catalytic hydrogenation of acetone is an important area of catalytic process to produce fine chemicals. Hydrogenation of acetone has important applications for heat pumps, fuel cells or in fulfilling the sizeable demand for the production of 2-propanol. Catalytic vapour phase hydrogenation of acetone has gained attention over the decades with variety of homogeneous catalysts notably Iridium, Rh, Ru complexes and heterogeneous catalysts comprising of Raney Nickel, Raney Sponge, Ni/Al2O3, Ni/SiO2, or Co-Al2O3, Pd, Rh, Ru, Re, or Fe/Al2O3 supported on SiO2 or MgO) and even CoMgAl, NiMg Al layered double hydroxide, Cu metal, CuO, Cu2O. Nano catalysts are developed for actone reduction Ni maleate, cobalt oxide prepared in organic solvents. Author present a review on acetone hydrogenation under different conditions with various homogeneous and heterogeneous catalysts studied so far in literature and new strategies to develop economic and environmentally benign approach. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)